Informed shared decision-making supported by decision coaches for women with ductal carcinoma in situ: study protocol for a cluster randomized controlled trial. Issue 1 (December 2015) - Berger-Höger, Birte; Liethmann, Katrin; Mühlhauser, Ingrid; Haastert, Burkhard; Steckelberg, Anke
Abstract Background Women with breast cancer want to participate in treatment decision-making. Guidelines have confirmed the right of informed shared decision-making. However, previous research has shown that the implementation of informed shared decision-making is suboptimal for reasons of limited resources of physicians, power imbalances between patients and physicians and missing evidence-based patient information. We developed an informed shared decision-making program for women with primary ductal carcinoma in situ (DCIS). The program provides decision coaching for women by specialized nurses and aims at supporting involvement in decision-making and informed choices. In this trial, the informed shared decision-making program will be evaluated in breast care centers. Methods/Design A cluster randomized controlled trial will be conducted to compare the informed shared decision-making program with standard care. The program comprises an evidence-based patient decision aid and training of physicians (2 hours) and specialized breast care and oncology nurses (4 days) in informed shared decision-making. Sixteen certified breast care centers will be included, with 192 women with primary DCIS being recruited. Primary outcome is the extent of patients' involvement in shared decision-making as assessed by the MAPPIN-Odyad (Multifocal approach to the 'sharing' in shared decision-making: observer instrument dyad). Secondary endpoints include the sub-measures of the MAPPIN-inventory (MAPPIN-Onurse, MAPPIN-Ophysician, MAPPIN-Opatient, MAPPIN-Qnurse, MAPPIN-Qpatient and MAPPIN-Qphysician ), informed choice, decisional conflict and the duration of encounters. It is expected that decision coaching and the provision of evidence-based patient decision aids will increase patients' involvement in decision-making with informed choices and reduce decisional conflicts and duration of physician encounters. Furthermore, an accompanying process evaluation will be conducted. Discussion To our knowledge, this is the first study investigating the implementation of decision coaches in German breast care centers. Trial registration Current Controlled TrialsISRCTN46305518, date of registration: 5 June 2015.